Abrogation of Article 370 of the Indian Constitution: An Analytical Study (Global Journal of Human-Social Science, 2021)
Architects of the Indian constitution were eager to make the country sovereign stable, peaceful and to protect the human rights of people. Constitutional laws contributed a very pivotal role to make the country's judicial system on right track for the sake of country's present ground reality complex scenarios and the future has been made secured for our parliamentary system is based on upgrading or new constitutional laws. But controversial Article 370 has provided the Jammu and Kashmir state vast powers as the autonomous body which created many complex problems including the threat of unity of the country and our government bifurcated the state into two successors "Union Territories" with additional limited aboriginal administrative powers under the Central Government. This Article was a "Temporary Provision" and it was essential to abrogate, modify and to eliminate this article. Article 370 has a historical background that does not emerge from legal or constitutional dimensions but it has complex political and religious dimensions that have an impact on the international border highly complex issues between India and Pakistan. Pakistan's government has been claiming over J&K since 1947. Dispute of L.A.C.
Keywords: the constitution of india; the valley of kashmir (jammu- kashmir; and ladakh); article 370; temporary provisions; union territories